The Discourse about Kosovo in Bosnia-Herzegovina, 1981–1989 - Kamberović Husnija (Comparative Southeast European Studies, 2021)
The author analyses the discourse about Kosovo in Bosnia and Herzegovina (BiH) during the 1980s. During these years, Serbian media developed several stereotypes to discredit the political leaders of BiH and accuse them of fomenting unrest in Kosovo. The author assesses these stereotypical depictions as well as the response of the Islamic Community and political leadership in BiH to these accusations. He asks what the attitude of Serbia’s political elite towards BiH was, and what role the Serbian political leadership played in the media attacks. He then investigates the evolution of the BiH leadership’s stances towards the events in Kosovo between the beginning and the end of the 1980s. And finally, through a close reading of session minutes and media, he assesses the increasingly deviating views of the BiH political leaders vis-á-vis the situation in Kosovo.